2003
DOI: 10.1038/sj.cgt.7700640
|View full text |Cite
|
Sign up to set email alerts
|

Improved gene transfer selectivity to hepatocarcinoma cells by retrovirus vector displaying single-chain variable fragment antibody against c-Met

Abstract: Engineered retroviruses are widely used vectors for cancer gene therapy approaches. However, the ability to target cells of therapeutic interest while controlling the expression of the transferred genes would improve both the efficiency and the safety of viral vectors. In this study, we investigated the ability of a retroviral amphotropic envelope displaying single-chain variablefragment (scFv) directed against the c-Met receptor, to target the entry of recombinant retroviruses to human hepatocarcinoma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
(49 reference statements)
0
32
0
Order By: Relevance
“…Multi-targeted kinase inhibitors to target c-MET together with VEGFR2 (XL880; Exelixis Inc., San Francisco, CA, USA) is also currently under development. Moreover, antibody approach to inhibit the c-MET/HGF pathway is also under investigation, both using antibodies against the ligand (Burgess et al, 2006) as well as the receptor (Nguyen et al, 2003). was used to downregulate c-MET expression in SCLC NCI-H69 cells in growth media containing 10% FCS as described previously (Ma et al, 2003a.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-targeted kinase inhibitors to target c-MET together with VEGFR2 (XL880; Exelixis Inc., San Francisco, CA, USA) is also currently under development. Moreover, antibody approach to inhibit the c-MET/HGF pathway is also under investigation, both using antibodies against the ligand (Burgess et al, 2006) as well as the receptor (Nguyen et al, 2003). was used to downregulate c-MET expression in SCLC NCI-H69 cells in growth media containing 10% FCS as described previously (Ma et al, 2003a.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other anti-MET antibodies that may activate MET signaling (23,24), onartuzumab was designed to be monovalent, to avoid agonistic activity (25), and it blocks the binding between MET and HGF (26,27). Onartuzumab is produced in Escherichia coli and does not have antibody-dependent cellular cytotoxicity (ADCC; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted infection by vaccinia virus, retrovirus and measles virus displaying singlechain antibody-binding sites (scFv) incorporated into their structure by fusion with viral envelope proteins has been described. [14][15][16][17][18][19][20][21][22] Bridging, bispecific targeting molecules comprising either an anti-adenovirus scFv or the Coxsackievirus-adenovirus receptor linked to a targeting scFv, have been used for targeting oncolytic adenoviruses. [23][24][25][26][27][28][29] Results from a number of studies with HSV-1 have shown that it is possible to alter the tropism by incorporating ligands such as erythropoietin, interleukin (IL) 13, human hepatitis B virus preS1 peptide, the N-terminal fragment of urokinase-type plasminogen activator or 6-His into the viral envelope as glycoprotein fusion proteins.…”
Section: Introductionmentioning
confidence: 99%